Affirmative action quotas in Brazilian higher education: Analyzing claims and implications. Issue 2 (3rd June 2014) - Kirakosyan, Lyusyena
Abstract : Purpose: – The purpose of this study is to address its drastic socioeconomic inequality and to compel its higher education institutions to diversify significantly while democratizing access to those schools. Brazil recently passed a sweeping affirmative action law requiring its public universities to reserve half of their available spots for low-income and non-White students. This article examines the underlying assumptions and implications of Brazil's adoption of affirmative-action quotas for higher education. Design/methodology/approach: – The article offers comparative analysis of Brazil's efforts with the experiences with quota and diversity policies in higher education in other countries. Findings: – It can be contended that, while the recent quota law in Brazil represents an important step in addressing socioeconomic and political inequalities, the measure is too limited in scope to empower historically disadvantaged populations and diminish future inequalities confronting these populations. This article concludes by underscoring the importance of efforts to develop a more comprehensive framing of affirmative action and diversity policies in Brazil's higher education, along with a simultaneous reform of public secondary education in the nation. Originality/value: – The article considers experiences with educational quotas in other countries and draws some useful comparisons and parallels to the Brazilian case.